Perlindungan Hukum Terhadap Pasien Menurut Peraturan Menteri Kesehatan Nomor 20 Tahun 2019 Tentang Penyelenggaraan Pelayanan Telemedicine Antar Fasilitas Pelayanan Kesehatan - Fauzullail, Ahmad Rifki; Irfan, Muhammad (Private Law, 2024)
The purpose of the study is to analyze the type of legal protection for patients in telemedicine services in Indonesia according to Minister of Health Regulation number 20 of 2019 concerning the implementation of telemedicine services between health service facilities, and To analyze what the legal responsibilities of doctors are in telemedicine services. This research uses a type of normative legal research method with a statute approach and a conceptual approach. The research results show that Minister of Health Regulation Number 20 of 2019 does not specifically regulate legal protection for patients in telemedicine, but the regulation only regulates the rights and obligations of providers and requesters of telemedicine services as contained in Article 18 paragraphs (1) and (2). This can certainly be a reference for legal protection for patients who carry out online consultations. However, it is explicitly regulated in Article 66 of Law Number 29 of 2004. The doctor's responsibility is divided into 3, namely civil responsibility based on Article 66 paragraph (3) of Law Number 29 of 2004, criminal responsibility based on Article 75, article 76, and Article 79 of Law Number 29 of 2004, and administrative legal responsibility based on Article 69 of Law Number 29 of 2004.